Thoughts on Management Accounting Research at The Accounting Review ’s Centennial - Labro, Eva (The Accounting Review, 2025)
ABSTRACT On the occasion of The Accounting Review’s centennial, I bring renewed urgency to the need for management accounting research to have practical relevance given the budgetary pressures on higher education. Practically relevant research is also relevant in the classroom. I present three ideas to increase the practical and teaching relevance of management accounting research. First, study the heterogeneity in management accounting practices across industries and embrace single-industry research deep dives. Second, focus on the role of management accounting in decision-making, planning, and forecasting. Third, explore the connections of management accounting with other subfields in accounting as well as other business disciplines.